A bibliometric analysis: Science education in a humanistic perspective - Abidin, Zaenal; Wibowo, Jayaman (Jurnal Mangifera Edu, 2024)
The aim of this research is to analyze the development of publications related to science education in a humanistic perspective. The method used in this research is bibliometric analysis using the VOSViewer application. Publication data is collected using the Publish or Perish application to obtain article data in journals indexed by Google Scholar. Data was obtained for 180 relevant articles from 2020 to 2024, that’s is because the author wants to see how big the development of educational research is, especially regarding humanistic-based science education after the Covid-19 pandemic. Of course, the development of learning strategies will feel much different after this pandemic. Therefore, it is hoped that this bibliometric analysis can become a reference in the development of a more relevant and comprehensive science education pattern. In 2020 there were 79 articles, in 2021 there were 29 articles, in 2022 there were 47 articles, and in 2023 there were 17 and in 20204 there were 8 articles. The research results show that there has been research development related to Science Education in a Humanistic Perspective. Topics that have recently been frequently discussed apart from the keywords used in searches are humanistic approach, science education, humanism, curriculum and contextual learning. However, there are several topics, such as sustainability, scientific literacy, science integrations, and the nature of science which are still rarely discussed, so they can become material for other researchers to develop research based on these topics.